Evaluación de los costos de producción de las tables de chocolate para la determinación de los resultados económicos en la corporación campesina "Pepa de oro", periodo 2011 - Tamayo Anchundia, Juana Mariuxi (2013)
The present investigation concerns the assessment of the costs of production of chocolate bars for the determination of economic performance in the corporation peasant "Pepa de Oro", Vinces town, province of Los Ríos, period 2011. Nowadays, agricultural enterprises thrive in a highly competitive world market, so companies have been forced to seek strategies that will allow them to meet the challenges of the same. These include compliance with standards and requirements made, low production costs, ensuring the quality of finished product and generating competitive advantages and greater demands in terms of human talent. Such is the case of chocolate processing companies that use cocoa as a raw material. Cocoa is processed in the corporation peasant “Pepa de Oro" , the same that is transformed into chocolate bars , is the product obtained by mixing sugar with two products derived from manipulating cocoa beans : a solid ( the cocoa paste) and a fat (cocoa butter) . From this basic combination are elaborated chocolate bars, which depend on the ratio of these elements and their mixture or not with other products such as milk and nuts. The research was conducted in order to identify the methodologies that allow verifying production costs versus the value thereof, to avoid deficiencies thereby accounting and administrative process, and that no future losses. Deepening the inquiry from the perspective of cost accounting is an academic interest that drives provide innovative procedures. In the professional field , as research in the field of engineering in accounting and auditing , the interest is to know the procedures and methods in the work context as independent variables of the requirements requested in practice. In the framework of the theory, the research was carried out according to the variables, dimensions and sub-dimensions of the theme. The techniques used were field observation and documentary survey of leaders, staff and customers of the corporation, the same data showed that were expressed in tables and charts, which helped analyze the results of the research work. The division of labor was done according to the needs that arose during the development of the rese